2013
DOI: 10.4187/respcare.02439
|View full text |Cite
|
Sign up to set email alerts
|

Upper and Lower Limb Muscles in Patients With COPD: Similarities in Muscle Efficiency But Differences in Fatigue Resistance

Abstract: BACKGROUND: Peripheral muscle dysfunction is a common finding in patients with COPD; however, the structural adaptation and functional impairment of the upper and lower limb muscles do not seem to be homogenous. We compared muscle fatigue and recovery time between 2 representative muscles: the middle deltoid and the quadriceps femoris. METHODS: Twenty-one subjects with COPD (FEV 1 46.1 ؎ 10.3% of predicted) underwent maximal voluntary isometric contraction and an endurance test (60% of maximal voluntary isomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
3
12
0
1
Order By: Relevance
“…These ratings on dyspnea and muscle fatigue are comparable to the ratings of perceived exertion (arm 5 [SD 2.5], leg 4 [SD 3.1]) reported by Robles et al [8]. Furthermore, Miranda et al [31] investigated the fatigability of the quadriceps muscle during an isometric knee extension exercise performed at 60 knee flexion and the middle deltoid during an isometric shoulder abduction exercise performed with the shoulder placed at Is the hypothesis/aim/objective of the study clearly described? 90 abduction.…”
Section: Resistance Exercisessupporting
confidence: 82%
See 1 more Smart Citation
“…These ratings on dyspnea and muscle fatigue are comparable to the ratings of perceived exertion (arm 5 [SD 2.5], leg 4 [SD 3.1]) reported by Robles et al [8]. Furthermore, Miranda et al [31] investigated the fatigability of the quadriceps muscle during an isometric knee extension exercise performed at 60 knee flexion and the middle deltoid during an isometric shoulder abduction exercise performed with the shoulder placed at Is the hypothesis/aim/objective of the study clearly described? 90 abduction.…”
Section: Resistance Exercisessupporting
confidence: 82%
“…They found a greater decline in median frequency throughout an isometric local muscle endurance test at 60% of maximal voluntary contraction for the middle deltoid compared to the quadriceps femoris. When corrected for time of the endurance test, the dyspnea and fatigue scores were higher for the middle deltoid during the isometric shoulder abduction exercise than for the quadriceps femoris during the isometric knee extension exercise [31].…”
Section: Resistance Exercisesmentioning
confidence: 89%
“…9 In a recent study done by Eduardo FM et al in 2014 observed that mid-thigh muscle area {Mid-thigh muscle area = mid-thigh circumference in cm* (0.314 *anterior thigh skin-fold in cm) 2 /(4* 3.14)} was significantly low in COPD patients. 10 There was no statistically significant difference seen in serum protein level between COPD cases and control group (p = 0.308). There was no significant difference seen between severities of disease.…”
Section: Discussionmentioning
confidence: 79%
“…No supporting evidence could be found in the literature on the relationship between leg strength and arm exercise capacity; however, previous studies have compared upper body strength with lower body strength and upper body aerobic capacity with lower body aerobic capacity in CRD. Recently, Miranda et al 27 compared middle deltoid and quadriceps femoris strength and endurance of 21 CRD patients with a mean FEV 1 of 46.1 ± 10.3% predicted. The researchers found deltoid and quadriceps to be similar with regard to absolute strength (similar differences when compared to healthy controls), but quadriceps had higher fatigability, indicating better upper body muscle (deltoid) fatigue resistance.…”
Section: Discussionmentioning
confidence: 99%